Composição química e percentual de adequação da dieta dos servidores do instituto nacional de pesquisas da Amazônia, Manaus, AM, Brasil - Nagahama, Dionísia; Yuyama, Lucia Kiyoko Ozaki; Aguiar, Jaime Paiva Lopes; Macedo, Sonja H. Madeira; Yonekura, Lina; Alencar, Fernando Hélio; Fávaro, Déborah Inês Teixeira; Afonso, Claudia; Vasconcellos, Marina Beatriz Agostini (Acta Amazonica, 2002)
The chemical composition of the duplicate food collections obtained from 36 servers of the National Institute of Researches of Amazônia (INPA) was evaluated and as percentage of recommended intake. The most frequently food consumed they were: sugar (91.7%), rice (80.6%), coffee (77.8%), milk (72.3%), bovine meat and bread (63.9%), cassava flour (58.4%), potato (55.6%), bean (50.0%), birds (38.9%), banana, carrot and sausages (33.4%), egg, sodas and tomato (30.6%). The results obtained showed the caloric deficiency of 40% and 52,7% respectively for adult men and adult women (25 to 50 years), protein of 76,4% (men) and 96,3% (women). The minerals Ca, Mg and Zn (men) were deficient whit an adequacy of about 50%. When compared with the recommended intakes, Fe was deficient for the adult women (59.4%). The minerals Na, Cu, Cl, Cr and I values were very high. Although of the great variety of foods ingested by this population, it was verified values are near the lowest limited set by RDA for most of the nutrients. Same belonging at a more privileged socio-economic living conditions, it is patent the importance of the alimentary orientation to that population group, because it is one of the main points in what it concerns the conditions of health and nutrition of the population.
Chemical composition and adequacy percentile of the servers feeding of the national Institute of Amazonia research, Manaus, AM., Brazil
Keywords: Diet; Adult; Chemical Composition; Nutritional Assessment; Dieta; Adulto; Composição Química; Avaliação Nutricional